2015
DOI: 10.3892/etm.2015.2256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and therapeutic evaluation of childhood myasthenia gravis

Abstract: This study aimed to analyze the clinical characteristics, classification and treatment of childhood myasthenia gravis (MG) and address the prognosis through follow-up. The clinical data of 135 children with MG were grouped according to clinical type and therapeutic drugs, retrospectively analyzed and prospectively monitored. Of the 135 MG patients, 85.2% had type I (ocular type), with only 4.2% progressing to systemic MG; 13.4% had type II (general type); and 1.5% had type III (fulminating type). Relapse occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Consistent with previous studies ( 6 , 11 ), we found that 96.2% of the patients presented with ocular symptoms only at onset, ptosis was the most common symptom, and 86.6% remained with OMG at the end of point when we followed up 164 cases for longer than 2 years. Similar to previous study ( 13 ), thyroid-related abnormalities and family history of autoimmune diseases were common in our study, indicating thyroid function as well as the related autoantibodies should be examined routinely for CMG patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous studies ( 6 , 11 ), we found that 96.2% of the patients presented with ocular symptoms only at onset, ptosis was the most common symptom, and 86.6% remained with OMG at the end of point when we followed up 164 cases for longer than 2 years. Similar to previous study ( 13 ), thyroid-related abnormalities and family history of autoimmune diseases were common in our study, indicating thyroid function as well as the related autoantibodies should be examined routinely for CMG patients.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies from China reported an AChR-Abs positivity rate between 40% and 78% ( 6 , 13 ), while this rate was relatively higher in other countries ( 8 , 14 ). In our current study, the positivity rate of AChR-Abs was 42.5%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Corticosteroid, steroid sparing agents like azathrioprine, cyclosporine A, cyclophosphamide even plasma exchange / IVIG administration had been tried in some studies and showed promising results. Prednisone and prednisolone are the first-line therapy in children with persisting symptoms with the starting dosage is 0.5-1mg/kg (maximum 30 mg/day), with a possible increase up to 2 mg/kg/day (maximum 60-80mg/day) [31].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] In ►Table 1, demographic profile of children with JMG (both generalized and ocular) has been shown as per studies in different populations. 7,[13][14][15][16] These epidemiological differences suggest the effect of both genetic and environmental factors on type and severity of myasthenia, which might affect therapeutic aspects and prognosis of this disorder.…”
Section: Epidemiologymentioning
confidence: 99%